The Academic Skills Model: The value of program mapping to support students’ literacies - Charlton, Nicholas; Hart, Christopher; Somers, Julie; Martin, Averil; Bosman, Caryl (Journal of Academic Language and Learning, 2022)
Transferrable skills (literacies) and employability have been a focus within the higher education sector in the 21st century. To assess where (and if) these required literacies are embedded, and how well students are supported in developing the required literacies in a bachelor program at an Australian university, academic, information and digital literacy mapping was conducted across the program through a partnership between library professionals and academics. The mapping in core courses of learning outcomes and assessment items to required literacies was conducted using the Academic Skills Model (ASM) (Charlton & Martin, 2018), which was designed to guide the development of academic, information and digital literacies in students. The literacy mapping found a range of academic and information literacies were scaffolded and supported in first and second-year courses across the program, but support for the development of few digital literacies were evident at any level. Consequently, these findings indicate that there are opportunities to embed more instruction in the digital literacies space. We posit that these results reflect a common assumption at the university level that students will be able to choose and effectively use the technologies needed for their assessment tasks, and hence may reflect an instructional gap that is worth investigating in other programs and universities. More generally, the results illustrate the utility of using the ASM to visualise where literacies are being incorporated throughout a program of study and what gaps exist for further inclusion to develop transferrable skills required for graduate employability.